In vivo Pharmacokinetic and Anticancer Studies of HH-N25, a Selective Inhibitor of Topoisomerase I, and Hormonal Signaling for Treating Breast Cancer - Lawal B; Kuo YC; Sumitra MR; Wu ATH; Huang HS (Dove Medical Press, 2021)
Bashir Lawal,1,2,* Yu-Cheng Kuo,3,4,* Maryam Rachmawati Sumitra,1,2 Alexander TH Wu,5- 8 Hsu-Shan Huang1,2,8- 10 1PhD Program for Cancer Molecular Biology and Drug Discovery, College of Medical Science and Technology, Taipei Medical University and Academia Sinica, Taipei, 11031, Taiwan; 2Graduate Institute for Cancer Biology & Drug Discovery, College of Medical Science and Technology, Taipei Medical University, Taipei, 11031, Taiwan; 3Department of Pharmacology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, 11031, Taiwan; 4School of Post-Baccalaureate Chinese Medicine, College of Chinese Medicine, China Medical University, Taichung, 40402, Taiwan; 5The PhD Program of Translational Medicine, College of Medical Science and Technology, Taipei Medical University, Taipei, 11031, Taiwan; 6Clinical Research Center, Taipei Medical University Hospital, Taipei Medical University, Taipei, 11031, Taiwan; 7TMU Research Center of Cancer Translational Medicine, Taipei Medical University, Taipei, 11031, Taiwan; 8Graduate Institute of Medical Sciences, National Defense Medical Center, Taipei, 11490, Taiwan; 9School of Pharmacy, National Defense Medical Center, Taipei, 11490, Taiwan; 10PhD Program in Drug Discovery and Development Industry, College of Pharmacy, Taipei Medical University, Taipei, 11031, Taiwan*These authors contributed equally to this workCorrespondence: Alexander TH Wu; Hsu-Shan Huang Email chaw1211@tmu.edu.tw; huanghs99@tmu.edu.twPurpose: Breast cancer is the most frequently diagnosed cancer globally, and the leading cause of cancer-associated mortality among women. The efficacy of most clinical chemotherapies is often limited by poor pharmacokinetics and the development of drug resistance by tumors. In a continuing effort to explore small molecules as alternative therapies, we herein evaluated the therapeutic potential of HH-N25, a novel nitrogen-substituted anthra[1,2-c][1,2,5]thiadiazole-6,11-dione derivative.Methods: We evaluated the in vivo pharmacokinetic properties and maximum tolerated dose (MTD) of HH-N25 in rats. We also characterized the compound for in vitro and in vivo anticancer activities and its inhibitory effects against DNA topoisomerases and hormonal signaling in breast cancer. Furthermore, we used molecular docking to analyse the ligand-receptor interactions between the compound and the targets.Results: The maximum serum concentration (Cmax), half-life (t1/2 beta), mean residence time (MRT), oral clearance (CL/f), and apparent volume of distribution (VD/f) of HH-N25 were 1446.67 ± 312.05 ng/mL, 4.51 ± 0.27 h, 2.56 ± 0.16 h, 8.32 ± 1.45 mL/kg/h, and 1.26 ± 0.15 mL/kg, respectively, after single-dose iv administration at 3 mg/kg body weight. HH-N25 had potent anticancer activity against a panel of human breast cancer cell lines with 50% inhibitory concentrations (IC50) ranging 0.045± 0.01∼ 4.21± 0.05 μM. The drug also demonstrated marked in vivo anticancer activity at a tolerated dose and prolonged the survival duration of mice without unacceptable toxicities based on body weight changes in human tumor xenograft models. In addition, HH-N25 exhibited a dose-dependent inhibition of topoisomerase I and ligand-mediated activities of progesterone and androgen receptors.Conclusion: HH-N25 represents a new molecular entity that selective suppressed TOP1 and hormonal signaling, and shows potent antitumor activities in human breast cancer cells in vitro and in vivo. HH-N25 thus represents a promising anticancer agent that warrants further preclinical and clinical exploration.Keywords: pharmacokinetic, anticancer activities, HH-N25, topoisomerase inhibition, hormonal signaling